Detective camp (A to Z mysteries.Super edition, 1,, 2009)
While learning detective skills at a sleep-away camp, Dink and his friends undercover a real mystery involving stolen paintings.

White House white-out (A to Z mysteries.Super edition, 3,, 2008)
When Dink, Josh, and Ruth Rose visit Washington, D.C., just before Christmas, they are inadvertently caught up in a kidnapping plot that was intended for the president's dog, but also involves the president's stepdaughter and her friend Marshall.

The New Year dragon dilemma (A to Z Mystery Super Edition, ,, 2011)
Dink, Josh, and Ruth Rose are enjoying a visit to San Francisco when Holden, their college-age tour guide, is accused of abducting Miss Chinatown from the Chinese New Year parade and stealing her valuable crown.

Mayflower treasure hunt (A to Z mysteries.Super edition, 2,, 2009)
When Dink, Josh, and Ruth Rose visit Plymouth, Massachusetts, for Thanksgiving, they uncover a mystery that dates back to the landing of the Pilgrims.

April Fools' fiasco (A to Z mysteries.Super edition, 9,, 2017)
"Mr. Paskey, owner of the Book Nook, plays an April Fools' Day prank on Dink, Josh, and Ruth Rose. They hatch a plan to get back at him, but then the bookstore is robbed--no joke! Can the kids track down the crook? Or will this April Fools' be an April fail?"--

Sleepy Hollow sleepover (A to Z Mystery Super Edition, ,, 2022)
Dink, Josh, and Ruth Rose are enjoying Halloween fun in Sleepy Hollow, New York, but when unplanned spooky things start happening, they investigate whether a real headless horseman might be to blame.

Secret admirer (A to Z mysteries.Super edition, 8,, 2015)
"Dink, Josh, and Ruth Rose solve a Valentine's Day mystery"--

The castle crime (A to Z Mystery Super Edition, ,, 2014)
While visiting London, Dink, Josh, and Ruth Rose solve a mystery and meet the Queen.

Crime in the crypt (A to Z mysteries.Super edition, 13,, 2022)
"When Ruth Rose's grandmother is accused of stealing, it's up to Dink, Josh, and Ruth Rose to clear her name"--

Grand Canyon grab (A to Z mysteries.Super edition, 11,, 2019)
The star of their favorite television show is kidnapped at the Grand Canyon, and it is up to Dink, Josh, and Ruth Rose to find him.

Operation orca (A to Z mysteries.Super edition, 7,, 2015)
"Dink, Josh, and Ruth Rose must solve a mystery when they go whale watching in Alaska"--

Space shuttle scam (A to Z mysteries.Super edition, 12,, 2022)
Dink, Josh, and Ruth Rose head to Florida where they uncover a scam at a local space memorabilia attraction.

Colossal fossil (A to Z mysteries.Super edition, 10,, 2018)
"Dink, Josh, and Ruth Rose solve a mystery at the Museum of Science"--

Leopard on the loose (A to Z mysteries.Super edition, 14,, 2022)
"When a leopard goes missing at the San Diego Zoo, it's up to Dink, Josh, and Ruth Rose to find her!"--